The antibacterial activity of polyoxometalates: structures, antibiotic effects and future perspectives. Issue 10 (22nd January 2018) - Bijelic, Aleksandar; Aureliano, Manuel; Rompel, Annette
Abstract : This Feature Article focuses on the antibacterial activity of POMs and POM-based hybrid and nanocomposite structures highlighting recent advances in the synthesis of biologically active POM systems and providing the state of the art in this research field. Abstract : Polyoxometalates (POMs) are, mostly anionic, metal oxide compounds that span a wide range of tunable physical and chemical features rendering them very interesting for biological purposes, an continuously emerging but little explored field. Due to their biological and biochemical effects, including antitumor, -viral and -bacterial properties, POMs and POM-based systems are considered as promising future metallodrugs. In this article, we focus on the antibacterial activity of POMs and their therapeutic potential in the battle against bacteria and their increasing resistance against pharmaceuticals. Recent advances in the synthesis of POMs are highlighted, with emphasis on the development and properties of biologically active POM-based hybrid and nanocomposite structures. By analysing the antibacterial activity and structure of POMs, putative mode of actions are provided, including potential targets for POM–protein interactions, and a structure–activity-relationship was established for a series of POMs against two bacteria, namely Helicobacter pylori and Streptococcus pneumoniae.